Studentsâ Attitudes to Learning Mathematics with Technology at Rural Schools in Sabah, Malaysia - Eng, Chin Kin; Han, Crispina Gregory K.; Fah, Lay Yoon (ASPENSI, 2011)
ABSTRACT: The purpose of this study was to investigate studentsâ attitudes to learning Mathematics with Technology at rural Secondary Schools in Sabah, Malaysia. This study involved 17 Secondary rural and non-rural Secondary Schools in Sabah.Â A total of Â 613 Â Form 4, Form 2, and Form 1 students were randomly chosen as respondents. Descriptive and inferential statistics were used to analyze the collected data. The reliability of the instrument was analyzed by using the Statistical Packages for Social Sciences (SPSS) version 13.0 for Windows. Descriptive statistical analysis showed that only 13.0% of rural Secondary School students possessed positive attitude to learning Mathematics with Technology as compared to 21.5% of students from non-rural Secondary Schools. Results of independent sample t-test has indicated that there was a significant difference (t = -2.424, df = 543, p < 0.05) in attitudes to learning Mathematics with Technology between rural and non-rural school students. Students from non-rural Secondary Schools possessed higher Confidence with Technology compared to students from rural schools. Inferentional statistical analysis also showed that there was no significant difference in studentsâ attitudes to learning Mathematics with Technology based on gender, streaming, and level of schooling. Therefore, Mathematics teacher is the main factors in how technology is used in classroom. Finally, school administrators should encourage Mathematics teacher to use ICT (Information and Communication Technology) widely to enhance their teaching.Â KEY WORD: Studentsâ attitudes, learning Mathematics with technology, rural Secondary Schools, and Mathematics teachers.Â Â Â Â About the Authors: Chin Kin Eng, Crispina Gregory K Han, and Dr. Lay Yoon Fah are Lecturers at the School of Education and Social Development UMS (Malaysia University of Sabah),Â Jalan UMS, 88400 Kota Kinabalu, Sabah, Malaysia. They can be reached at: sportychin@yahoo.com, pieces.cris@yahoo.com, and layyoonfah@yahoo.com.myHow to cite this article? Eng, Chin Kin, Crispina Gregory K. Han & Lay Yoon Fah. (2011). âStudentsâ Attitudes to Learning Mathematics with Technology at Rural Schools in Sabah, Malaysiaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.1(2) Desember, pp.247-262. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, ISSN 2088-1290.Chronicle of the article: Accepted (October 22, 2011); Revised (November 26, 2011); and Published (December 15, 2011).